IMPROVEMENT OF THE PRODUCTION TECHNOLOGY OF COMPLEX KNITTED SUIT FABRICS WITH MIXED COMPOSITION - Kholmirzayev Erkaboy Abdurakhmon oglu; Siddikov Patkhillo Siddiqovich (American Journals Publishing, 2025)
This article is intended for the production of currently relevant mixed-composition suit fabrics and describes the wide application of this technology to manufacturing enterprises throughout our Republic and the possibility of increasing economic efficiency and producing quality products.